Paleoecology of naticid–molluscan prey interaction during the Late Jurassic (Oxfordian) in Kutch, India: evolutionary implications. (September 2021) - Bardhan, Subhendu; Saha, Sandip; Das, Shiladri S.; Saha, Ranita
Abstract: We document and quantify one of the oldest predator–prey interactions between naticid gastropods and molluscan prey, on the basis of drill holes in shells, from the Late Jurassic (Oxfordian) beds of Kutch, western India. Previously, many workers recorded naticid-like drill holes on prey taxa from the Triassic and the Jurassic, but in the absence of associated naticid body fossils, they remained equivocal. The present gastropod community is dominated by turritellines (98% of the sample) that form the turritelline-dominated assemblage, and the naticid drilling predation is restricted almost entirely to turritellines among gastropods. Confamilial naticid predation takes place occasionally. Within the bivalve community, corbulids and nuculids are most abundant and are drilled more often than other taxa. These observations indicate that prey selection was opportunistic and based solely on availability. Drilling intensities at both assemblage and lower taxon levels are low. Behavioral stereotypy of naticid predation in some cases is moderately high. Turritellines are often the preferred prey of naticid gastropods since the late Early Cretaceous. These two groups form a recurrent association reflecting prey–predator interaction. Here we suggest that both turritellines and naticids evolved during the Jurassic, and the prey–predator interaction between them was established shortly thereafter. Among bivalves, corbulids also became important prey of naticids in the same spatiotemporal framework. Corbulids are older than naticids and first appeared during the Middle Jurassic. After their first encounter with naticids, corbulids evolved conchiolin layers within the valves to resist predation.